2007
DOI: 10.1515/epoly.2007.7.1.1110
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Complexation of a Charged Dendrimer by Linear Polyelectrolyte: Computer Modelling

Abstract: Brownian-dynamics simulations have been performed for complexes formed by a charged dendrimer and a long oppositely charged linear polyelectrolyte when overcharging phenomenon is always observed. After complex formation the orientational mobility of the individual dendrimer bonds, the fluctuations of the dendrimer size, and the dendrimer rotational diffusion have been simulated. Corresponding relaxation times do not depend on the linear-chain length in a complex and are close to those for a single neutral dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 22 publications
(48 reference statements)
4
21
0
Order By: Relevance
“…The study of the DNA complexation by different transport agents is hugely important for many biomedical applications. [11][12][13][14] In our previous publications, we have already considered complexes formed by the flexible LPE chain and branched polymers (macroions) of different topology including star-like polymers, 15 dendrimers, [16][17][18][19] and irregular hyperbranched polymers. 20 For all of those complexes, the overcharging effect has been observed; i.e., the charge of the adsorbed part of a LPE exceeds that necessary for the neutralization of the macroion charge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the DNA complexation by different transport agents is hugely important for many biomedical applications. [11][12][13][14] In our previous publications, we have already considered complexes formed by the flexible LPE chain and branched polymers (macroions) of different topology including star-like polymers, 15 dendrimers, [16][17][18][19] and irregular hyperbranched polymers. 20 For all of those complexes, the overcharging effect has been observed; i.e., the charge of the adsorbed part of a LPE exceeds that necessary for the neutralization of the macroion charge.…”
Section: Introductionmentioning
confidence: 99%
“…24 The simulation results for complexes formed by a single dendrimer with charged terminal groups and a long flexible LPE agree qualitatively with theoretical predictions. [16][17][18][19] Our previous studies dealt with the complexes comprised by one macroion and one LPE chain. [15][16][17][18][19][20] However, one LPE can form a complex with several macroions.…”
Section: Introductionmentioning
confidence: 99%
“…29,30,32,33 This approach may be problematic when applied to dense structures such as dendrimers, where the Debye-Hückel approximation can easily break down as charges approach each other and their distance goes below the Bjerrum length. Indeed, recent computational studies of single charged dendrimers 22,23 with explicit counterions have clearly demonstrated that counterion condensation upon increasing strength of electrostatic interactions is able to cause noticeable changes in dendrimer's structure, which cannot be accounted for within the Debye-Hückel approximation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rather broad parameter space characterizing the actual systems, coarse-grained models have been widely utilized for the theoretical description and the computer modeling of such complexes [21][22][23][24][25][26][27][28][29][30][31][32]. These studies aimed at the elucidation of the generic behavior related to their conformational characteristics and to phenomena of key importance regarding their action as complexation agents and delivery vehicles, such as overcharging [27,31,33,34].…”
Section: Introductionmentioning
confidence: 99%